The role of SDN 251 Jamika library in supporting curriculum implementation - Ellyazar Swastiko (Himpunan Pengembang Kurikulum Indonesia, 2026)
The importance of libraries in strengthening literacy competencies, supporting curriculum implementation, and enriching the school learning environment needs to be highlighted. This study aims to analyze the role of school libraries in improving information literacy, supporting curriculum implementation, and enhancing the quality of learning at SDN 251 Jamika. Through structured interviews with librarians and teachers, this study examines library services, strategies for increasing student reading interest, the use of simple technology, and collaboration with teachers in literacy-based programs. The results show that the library at SDN 251 Jamika has made efforts to adapt to curriculum demands by providing relevant collections, implementing regular literacy activities, and developing programs that encourage active learning. The library has also begun utilizing basic technology for collection management and services. However, challenges such as limited facilities, book collections, and human resources remain obstacles that need to be overcome. This study contributes to educational practice by emphasizing the importance of strategic library management in improving elementary school students' literacy skills and strengthening the library's role as a central part of the school learning ecosystem. Abstrak Pentingnya perpustakaan dalam memperkuat kompetensi literasi, menunjang pelaksanaan kurikulum, serta memperkaya lingkungan belajar di sekolah perlu ditingkatkan. Penelitian ini bertujuan untuk menganalisis peran perpustakaan sekolah dalam meningkatkan literasi informasi, mendukung implementasi kurikulum, dan meningkatkan kualitas pembelajaran di SDN 251 Jamika. Melalui metode wawancara terstruktur dengan pustakawan dan guru, penelitian ini mengkaji layanan perpustakaan, strategi peningkatan minat baca murid, pemanfaatan teknologi sederhana, serta kolaborasi dengan guru dalam program berbasis literasi. Hasil penelitian menunjukkan bahwa perpustakaan di SDN 251 Jamika telah berupaya menyesuaikan diri dengan tuntutan kurikulum melalui penyediaan koleksi yang relevan, pelaksanaan kegiatan literasi secara rutin, dan pengembangan program yang mendorong pembelajaran aktif. Perpustakaan juga mulai memanfaatkan teknologi dasar untuk pengelolaan koleksi dan layanan. Namun demikian, tantangan seperti keterbatasan sarana, koleksi buku, dan sumber daya manusia masih menjadi hambatan yang perlu diatasi. Penelitian ini memberikan kontribusi terhadap praktik pendidikan dengan menekankan pentingnya manajemen perpustakaan yang strategis dalam meningkatkan keterampilan literasi murid sekolah dasar serta memperkuat peran perpustakaan sebagai bagian sentral dari ekosistem pembelajaran di sekolah. Kata Kunci: implementasi kurikulum; literasi informasi; perpustakaan sekolah